The Legal Certainty of Hotel Condominium Agreements Between PT. Banua Anugerah Sejahtera with The Owner of The Grand Banua Condotel - Susanto, Himawan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Hotel condominiums are accommodations that can be used as an alternative to support the high mobility of today's society. This has made Condotel grow rapidly in Indonesia, however, this development is not in line with the existence of clear legal regulations. The approach used in this paper is a sociological juridical approach, which is an approach by seeking information through direct interviews with informants empirically first and then proceeding with conducting research on secondary data contained in literature studies through theoretical steps. Based on the study in this paper it is known. The implementation of hotel condo agreements so far has not had a legal footing in Indonesia, this has resulted in many developers and builders often seeking large profits without heeding the principles of good ethics in buying and selling agreements and managing hotel condos. The weakness that makes the condo hotel agreement policy in Indonesia not fair is the weakness of laws and regulations in the form of non-regulation of the contents of the condo hotel agreement and the position of the condo hotel in Act No. 20 of 2011, this results in no oversight regarding the sale and purchase agreement. and management of hotel condominiums, so that many actors in the development and construction of hotel condominiums seek profit through sale and purchase agreements and management of hotel condominiums by excluding consumers or hotel condotel owners (condotel).Keywords: Assurance; Condominium; Hotel.